Meningkatkan Retensi Pengetahuan High Quality CPR dengan Self Directed Video - Achmad Sya'id (LPPM Universitas dr. Soebandi, 2019)
Mortality due to cardiac arrest are still can’t be managed. High quality cardio pulmonary resuscitation actually can save the victim if it’s done poperly, the knowledge about the high quality CPR should be owned by nursing students. Analysing the nursing student knowledge of high quality CPR retention after being exposed to Self Directed Video (SDV). Quasy experimental design, one group pre-post test was conducted on 32 samples. The nursing student knowledge about high quality CPR is assessed before SDV, same day after watching SDV, and 15th days after watching SDV. Before being exposed to SDV the knowledge is sufficient, then for same day and 15th days after watching SDV is good, (1st = 89.8750, 15th = 89.1250). By using paired t-test, p value is 0.012 <α (0.05), there is a significant effect of SDV on high quality CPR knowledge retention. When the steps of high quality CPR is packaged uniquely, absolutely it can increase the retention of that information.